Information warfare and electronic warfare systems - Poisel, Richard (Artech House electronic warfare library., 2013)
Information warfare is emerging as the new war fighting paradigm of the U.S. and many of its allies. This book is the first in the field to address communication electronic warfare (EW) systems in the context of information warfare. Authored by a recognized leading authority, the book includes a unique formulation of EW system performance and presents results of system simulations that have not appeared previously in any related literature. Essential reading for EW engineers and researchers working in defense, aerospace, and military capacities, the book explores the properties of information,